Self-harm in UK armed forces personnel: descriptive and case-control study of general hospital presentations. - Hawton, K; Harriss, L; Casey, D; Simkin, S; Harrison, K; Bray, I; Blatchley, N (2009)
BACKGROUND: Little is known about self-harm in the armed forces. AIMS: To investigate the characteristics of armed forces personnel presenting to a general hospital following self-harm and compare these with matched controls who had self-harmed. METHOD: Investigation of armed forces personnel presenting to hospital between 1989 and 2003 following self-harm and case-control comparison with people in the general population who had self-harmed. RESULTS: One hundred and sixty-six armed forces personnel presented with self-harm during the study period, of whom 72.3% (120) were male. Nearly two-thirds (62.7%) were aged under 25 years. Relationship problems (62.0%), employment problems (43.9%) and alcohol misuse (40.5%) were common. Fewer armed forces personnel than controls had evidence of current or past psychiatric disorders or treatment or a prior history of self-harm, and their suicidal intent was lower (males only). Of 64 people in the armed forces who presented during the first 9 years of the study period, 1 had died (from natural causes) by the end of 2000, compared with 9 (5.1%) of the controls, 6 by probable suicide. CONCLUSIONS: Self-harm by armed forces personnel may often be a response to interpersonal and employment problems complicated by alcohol misuse, with relatively low suicide intent.